Peran Pajak dalam Mewujudkan Praktik ESG: Strategi untuk Keberlanjutan Bisnis - Tiffany Lajira (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
In an era of business that is increasingly focused on sustainability, tax policy has become a critical element that can shape sustainable business practices. A deep understanding of the relationship between tax policy and ESG (Environmental, Social, and Governance) practices is key to forming a holistic and sustainable view in running a business. Sustainable tax policy has a strategic role in realizing ESG practices and improving the company’s financial performance. The implementation of a sustainable tax strategy can strengthen the company’s competitiveness in the market. Governments and companies must integrate sustainable tax policies into business and development strategies. ESG reflects an important shift in the business paradigm, where companies are not only pursuing financial gain, but are also responsible for the impact of their business operations on the environment, society, and good corporate governance. Awareness of these aspects has changed the way companies integrate responsibility. Research shows that incorporating ESG elements in investment decision making can help achieve the ideal balance between return and risk while benefiting society and the environment